INTELLECTUAL CAPITAL OF SOCIOECONOMIC AREA: MEASURE AND STRUCTURE - Jan Ostoj (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej)
This paper is the second in the series of three papers devoted to the estimated value of intellectual capital belonging to any socioeconomic area: province, municipality, country, region etc. An idea of the estimated value is based on the assumption that the value of a given socioeconomic area for its residents is determined by income generated due to the presence of a business activity in a given area. The structure of the presented method allows for covering all components of intellectual capital within estimated value regardless whether their existence is realized or not. The paper presents the valuation method of intellectual capital to be found in a given socioeconomic area for the purpose of using this method in the third part of the series in which estimates will be conducted for each individual voivodeship (province) in Poland.